Literature Review : Efek Genistein Terhadap Penyakit Osteoporosis - Fajrina Ramadhani (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Postmenopausal osteoporosis is a condition that increases fracture risk due to decreased bone mineral density (BMD). Hormone replacement therapy (HRT) is often restricted due to side effects, prompting the search for natural alternatives such as phytoestrogens, particularly genistein. Genistein is a major isoflavone in soy that has the potential to increase bone mineral density and improve bone metabolic balance. This study aims to review the effectiveness of genistein on bone health of postmenopausal women through a literature review of various clinical studies in the last 10 years. Results showed that genistein significantly increased bone mineral density, osteocalcin, bone-ALP, and decreased sclerostin. In addition, genistein positively impacts lipid profiles and blood glucose levels, and improves bone calcium retention, especially when combined with calcium and vitamin D3. A mixture of isoflavones in a natural ratio is more effective than single genistein. In conclusion, genistein is a safe and effective natural alternative in preventing and managing osteoporosis in postmenopausal women.